2013
DOI: 10.1111/spc3.12028
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the Expected, the Desired, and the Feared: Influences on Perceptual Interpretation and Directed Attention

Abstract: Though people often believe their visual experiences reflect the objective state of the surrounding world, a wealth of recent evidence suggests that perceptions are systematically biased. We draw from contemporary research and supplement with real world anecdotes to suggest that two aspects of perception are subject to influence by states internal to perceivers themselves. We focus on the biases that arise from two difficult tasks faced by the visual system. First, visual information is often unclear and ambig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 70 publications
(71 reference statements)
1
18
0
Order By: Relevance
“…Finally, our work extends research suggesting that motivated perceptions can have important implications (Riccio, Cole, & Balcetis, 2013). Indeed, across several studies in real-world and fictional contexts, we consistently found that perceptions of power differences mediated the effects of SDO on support for social policy.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, our work extends research suggesting that motivated perceptions can have important implications (Riccio, Cole, & Balcetis, 2013). Indeed, across several studies in real-world and fictional contexts, we consistently found that perceptions of power differences mediated the effects of SDO on support for social policy.…”
Section: Discussionsupporting
confidence: 81%
“…Further, perceived attractiveness might differ from rated attractiveness. Just as attitudes can be the result of motivated reasoning, so can perceptions (Balcetis & Dunning, 2006;Riccio, Cole, & Balcetis, 2013). Some work shows that motivated participants view ambiguous images in line with their expectations (Balcetis & Dunning, 2006).…”
Section: (Dis)similarity and Attractivenessmentioning
confidence: 99%
“…Further, perceived attractiveness might differ from rated attractiveness. Just as attitudes can be the result of motivated reasoning, so can perceptions (Balcetis & Dunning, 2006;Dunning & Balcetis, 2013;Riccio, Cole, & Balcetis, 2013). Some work shows that motivated participants view ambiguous images in line with their expectations (Balcetis & Dunning, 2006).…”
Section: (Dis)similarity and Attractivenessmentioning
confidence: 99%